Development of Domino Cards as A Social Science Learning Media on the Material of the Development of the Hindu-Buddhist Kingdom in Indonesia Based on Q. S. Yusuf Verse 111 At An-Nizam Private Middle School - Azhari, Syaidatul; Yusnaldi, Eka (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study uses a Research and Development (R&D) approach, which includes steps ranging from needs analysis, media design, product creation, expert validation, to student trials. The research findings show that the process of making domino cards is carried out systematically, resulting in learning media that are in accordance with the quality of the material and student requests. Domino card media is considered realistic and practical for use in social science education, according to topic experts and media professionals, as well as feedback from students. In addition, the results of the effectiveness test show that the use of domino cards can help students understand the material about the development of Hindu-Buddhist kingdoms in Indonesia, as evidenced by increased learning activity, and students' ability to understand concepts and learn lessons from history by integrating reflective values from Q.S. Yusuf verse 111.